Assessment Of Efficacy Of Intralesional Vitamin D3 Injection In The Treatment Of Recalcitrant Warts - Mohsin, Sadia; Mazhar, Hina; Naveed, Tehseen; Sahibzada, Anum (Journal of Rawalpindi Medical College, 2025)
Objective To assess the efficacy of intralesional vitamin D3 injection as a treatment modality for recalcitrant warts in a tertiary care setting in Pakistan. Materials and Methods This quasi-experimental study was carried out in the Department of Dermatology, CMH Lahore, over six months from March 16 to September 16, 2021. After obtaining approval from the hospital’s ethical and research committee, 139 patients aged 18–60 years, presenting with recalcitrant warts fulfilling the inclusion criteria, were recruited. Intralesional vitamin D3 (600,000 IU/mL), 0.5ml was injected into the base of up to four warts per session, with injections repeated every two weeks for a maximum of four sessions. Efficacy was defined as the complete resolution of all warts. Adverse events were monitored, and data were stratified by age, gender, and wart characteristics. Results The study population had a mean age of 30.3 ± 6.8 years, with a male predominance (57.6%). The average wart duration was 6.5 ± 1.5 months. Complete resolution was achieved in 89.9% of patients. While no statistically significant differences in efficacy were observed across stratified subgroups (p > 0.05), patients with shorter wart durations (3–6 months) demonstrated the highest success rate (98.7%), whereas those with warts lasting longer than 6 months showed the lowest response (79.0%). Adverse effects were minimal and resolved on their own, with 15% of patients experiencing injection site pain and 10% reporting temporary erythema. Conclusion Intralesional vitamin D3 injections have demonstrated significant efficacy and a favorable safety profile, positioning it as a promising and novel treatment for recalcitrant warts. However, to strengthen the evidence and better understand its long-term benefits, additional randomized controlled trials are essential.